2014
DOI: 10.1021/bi5008063
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Asymmetry and the Role of the Conserved Active-Site Thiol in Rabbit Muscle Creatine Kinase

Abstract: Symmetric and asymmetric crystal structures of the apo and transition state analogue forms, respectively, of the dimeric rabbit muscle creatine kinase have invoked an "induced fit" explanation for asymmetry between the two subunits and their active sites. However, previously reported thiol reactivity studies at the dual active-site cysteine 283 residues suggest a more latent asymmetry between the two subunits. The role of that highly conserved active-site cysteine has also not been clearly determined. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Unnatural amino acids (UAAs) have the potential to provide site-specific information about protein structure and dynamics (Getahun et al, 2003;Tucker et al, 2005;Schultz et al, 2006;Aprilakis et al, 2007;Jackson et al, 2007;Glasscock et al, 2008;Oh et al, 2008;Weeks et al, 2008;Miyake-Stoner et al, 2009;Taskent-Sezgin et al, 2009Waegele et al, 2009Waegele et al, , 2011Ye et al, 2009Ye et al, , 2010Fafarman & Boxer, 2010;Goldberg et al, 2010;Urbanek et al, 2010;Nagarajan et al, 2011;Thielges et al, 2011;Bazewicz et al, 2012Bazewicz et al, , 2013Peran et al, 2014;Petersson et al, 2014;Walker et al, 2014;Londergan et al, 2015;Tookmanian et al, 2015). Fundamentally, these spectroscopic reporter UAAs must contain a readily measurable spectroscopic signature that is sensitive to the local environment and must be able to be site-specifically incorporated into peptides or proteins with high efficiency and fidelity while being minimally intrusive.…”
Section: Introductionmentioning
confidence: 99%
“…Unnatural amino acids (UAAs) have the potential to provide site-specific information about protein structure and dynamics (Getahun et al, 2003;Tucker et al, 2005;Schultz et al, 2006;Aprilakis et al, 2007;Jackson et al, 2007;Glasscock et al, 2008;Oh et al, 2008;Weeks et al, 2008;Miyake-Stoner et al, 2009;Taskent-Sezgin et al, 2009Waegele et al, 2009Waegele et al, , 2011Ye et al, 2009Ye et al, , 2010Fafarman & Boxer, 2010;Goldberg et al, 2010;Urbanek et al, 2010;Nagarajan et al, 2011;Thielges et al, 2011;Bazewicz et al, 2012Bazewicz et al, , 2013Peran et al, 2014;Petersson et al, 2014;Walker et al, 2014;Londergan et al, 2015;Tookmanian et al, 2015). Fundamentally, these spectroscopic reporter UAAs must contain a readily measurable spectroscopic signature that is sensitive to the local environment and must be able to be site-specifically incorporated into peptides or proteins with high efficiency and fidelity while being minimally intrusive.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In the case of reporters, au nique spectroscopic signature that can be observed by fluorescence, [7][8][9][10] EPR, [11,12] NMR, [13,14] or vibrational spectroscopy [15][16][17] is required. In recent years vibrational UAA have been employed to study the local hydra-tion and the electrostatic environments of proteins by IR [18][19][20][21][22][23][24][25][26] and Raman spectroscopy. [26,27] Nitrilesa nd azides are arguably the two most important functional groups for vibrationalU AA becauseo ft heir small size, relative stability,s ensitivity,a nd absorptions that occur in an open window in the IR.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years vibrational UAA have been employed to study the local hydra-tion and the electrostatic environments of proteins by IR [18][19][20][21][22][23][24][25][26] and Raman spectroscopy. [26,27] Nitrilesa nd azides are arguably the two most important functional groups for vibrationalU AA becauseo ft heir small size, relative stability,s ensitivity,a nd absorptions that occur in an open window in the IR. [18,28] We recentlyr eported ad irect comparison of these two vibrational reportersa nd demonstrated that for many applicationsa zides are superior because they have as ignificantly larger extinction coefficient while maintaining excellent sensitivity to their local environment in terms of frequency shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, each site contains cysteine residues. It is implied the thiol group of cysteine that might play a role in the binding affinity [47][48][49] was generated by immunological methods and hybridoma screening which was selected specifically binding to the 35th to 66th amino acid residues of ORF3 protein. Therefore, further investigation of the amino acid sequence of the antigen-binding sites of mAb 7D3 would be interesting.…”
Section: Discussionmentioning
confidence: 99%